2022
DOI: 10.1108/ecam-05-2021-0445
|View full text |Cite
|
Sign up to set email alerts
|

Causes of cost overruns in building construction projects in Asian countries; Iran as a case study

Abstract: PurposeCost overruns have been identified as the most significant challenge for construction sector stakeholders. Like many developing countries, the Iranian construction industry suffers from poor cost performance. So, the current research aims to investigate the causes of cost overrun in Iranian construction projects. This paper also reviews the findings of similar studies conducted in several Asian countries.Design/methodology/approachThis paper includes a literature review and a quantitative method with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The construction industry plays a crucial role in the macroeconomic stabilization in developing countries (Noorzai, 2022;Parchami Jalal et al, 2021). While the completion of projects in the planned duration and cost can achieve this success, cost overrun is one of the main obstacles to infrastructure projects reaching the predetermined objectives (Amini et al, 2022). Flyvbjerg (2009) states the cost overrun in infrastructure projects is between 20.4 and 44.7%.…”
Section: Cost Overrun In Construction Industrymentioning
confidence: 99%
See 4 more Smart Citations
“…The construction industry plays a crucial role in the macroeconomic stabilization in developing countries (Noorzai, 2022;Parchami Jalal et al, 2021). While the completion of projects in the planned duration and cost can achieve this success, cost overrun is one of the main obstacles to infrastructure projects reaching the predetermined objectives (Amini et al, 2022). Flyvbjerg (2009) states the cost overrun in infrastructure projects is between 20.4 and 44.7%.…”
Section: Cost Overrun In Construction Industrymentioning
confidence: 99%
“…Previously, several studies have identified causes of cost overruns and ranked them with different approaches. These studies were carried out in various sections of Iran's construction industry, such as buildings (Amini et al, 2022), mega hospitals (Balali et al, 2020), and urban construction projects (Heravi and Mohammadian, 2021). Therefore, the authors conducted a study into cost overruns in Iranian water-related projects, considering the existing gap.…”
Section: Cost Overrun In Construction Industrymentioning
confidence: 99%
See 3 more Smart Citations